ECONOMIC GROWTH OF THE TOURISM SECTOR IN A COVID-19 PANDEMIC DURING 2021 - Žaklina; Stanisic, Snjezana (The European Journal of Applied Economics, 2021)
The tourism sector around the world has been hit hard by the covid-19 virus pandemic. The consequences of the pandemic during 2020 on the entire tourism sector have significantly reduced the income of both individuals and the collection in the state treasury. The introduced measures, as well as the mass vaccination of citizens, enabled the opening of tourist destinations during 2021, which brought long-awaited revenues to this branch of the economy. The opening of tourist destinations has started the travel sector, both air and road, rail and water transport. The aim of this paper is to analyze the current economic growth of the tourism sector and compare the current situation with the situation in 2019 and the situation during the crisis in 2020. The paper also gives an overview of the legal measures adopted in order to overcome the problems caused by the closure. The analysis of the economic growth of the tourism sector during 2021 was performed on the basis of available data and information both in the world and in the countries of the region. Also, the analysis was performed for both international tourism and domestic tourist destinations. Based on the conducted analysis, it is concluded that the number of tourists who visited the observed regions in the first half of 2021 is still lower compared to the same period in 2019.